Panhellenes at Methone : Graphê in Late Geometric and Protoarchaic Methone, Macedonia (ca 700 BCE) - Malkin, Irad; Strauss Clay, Jenny; Tzifopoulos, Yannis Z. (Trends in classics. Supplementary volumes ;, 2017)
This volume discusses the multidimensional aspects of the unique, and so far unprecedented for Macedonia, 191 sherds from Methone in Pieria, dated to ca 700 BCE, which bear inscriptions, graffiti, and (trade)marks inscribed, incised, scratched and rarely painted. The 191 vessels were unearthed during excavations in ancient Methone in Pieria, the oldest colony of Greeks from Eretria in the north according to tradition. The Methone find is unique for two reasons. First, most of the pottery dates between 730 and 700 BCE, a period from which very few examples of Greek writing survives. And second, inscribed ceramics, scratched or painted, are extremely rare in Macedonia. This new evidence of inscribed pottery from Methone is invaluable for classical studies, and the papers of this volume contribute notably to current discussions about: the Greeks and the Greek language in Macedonia; the Greek colonization; the pottery trade and the early Greek transport amphoras; trade, the symposium, and other contexts for the development of writing; the 'alphabets' of Methone and the introduction of the alphabet in Greece; the dialect(s) of Methone in relation to the Greek dialects; early Greek writing, literacy, and literary beginnings.